Development of a health education intervention strategy using an implementation research method to control taeniasis and cysticercosis in Burkina Faso - Helena Ngowi; Ivan Ozbolt; Athanase Millogo; Veronique Dermauw; Télesphore Somé; Paul Spicer; Lori L. Jervis; Rasmané Ganaba; Sarah Gabriel; Pierre Dorny; Hélène Carabin (BMC, 2017)
Abstract Background Taeniasis and cysticercosis are two diseases caused by Taenia solium, a parasite transmitted between humans and pigs, leading to considerable economic loss and disabilities. Transmission of the parasite is linked to environmental and behavioural factors such as inadequate sanitation and hygiene, poor pig management, and consumption of infected pork. This study used implementation research method to design a health education intervention strategy for reducing T. solium infections in Burkina Faso, a country endemic for the parasite. Methods Eighteen group discussions were conducted with 8-18 participants each in three villages. In addition, structured interviews were conducted among 4 777 participants and 2 244 pig owners, who were selected through cluster random sampling in 60 villages of three provinces of Burkina Faso. Both approaches assessed knowledge and practices related to T. solium. The information obtained was used to develop a community-adapted health education intervention strategy to control taeniasis and cysticercosis in Burkina Faso. Results The group discussions revealed that participants had a poor quality of life due to the diseases as well as inadequate access to latrines, safe water, and healthcare services. In addition, it was found that pig production was an important economic activity, especially for women. Furthermore, financial and knowledge constraints were important limitations to improved pig management and latrine construction. The survey data also showed that open defecation and drinking unboiled water were common behaviours, enhanced by a lack of knowledge regarding the transmission of the parasite, perceived financial barriers to the implementation of control measures, lack of public sensitization, as well as a lack of self-efficacy towards control of the parasite. Nevertheless, the perceived financial benefits of controlling porcine cysticercosis could be emphasized by an education program that discourages open defecation and encourages drinking safe water. The final intervention strategy included a Participatory Hygiene and Sanitation Transformation (PHAST) approach, as well as a 52-min film and an accompanying comic booklet. Conclusions The main problem in the study communities regarding the transmission of T. solium cysticercosis is the random disposal of human faeces, which can be contaminated with parasite eggs. Prevention of open defecation requires the building of latrines, which can be quite problematic in economically challenged settings. Providing the community with the skills to construct durable latrines using low-cost locally available materials would likely help to resolve this problem. Further studies are required to implement and evaluate the T. solium control strategy developed in this study.